Factors Affecting Audit Delay (An Empirical Study On Lq45 Listed Companies From 2020 To 2022) - Hardjowono, Theofani Eka Putri; Fachriyah, Nurul (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
This research aims to determine the relationship between independent variables, namely audit complexity, company type, profitability, and company size, with the dependent variable audit delay. The objects of the study are companies listed on the Indonesia Stock Exchange (IDX) and included in the LQ45 index during the period from 2020 to 2022. The research conducted falls under quantitative research, utilizing secondary data as samples. Using purposive sampling technique and multiple linear regression analysis with SPSS, the results indicate that factors such as industry type and profitability significantly influence audit delay. Meanwhile, audit complexity and company size do not affect audit delay.